Phosphatase Activity and Solubilization of Calcium phosphate by Phosphate Solubilizing Bacteria - SULIASIH SULIASIH; RAHMAT RAHMAT (Biodiversitas Journal of Biological Diversity, 2007)
A study was undertaken to investigate the ability of phosphate solubilizing bacteria to solubilize insoluble phosphate. Seventeenth phosphate solubilizing bacteria were isolated from soil in Wamena, Papua. These organism was identified as Bacillus sp, Bacillus pantothenticus, Bacillus megaterium, flavobacterium sp, Flavobacterium breve, Klebsiella aerogenes , Chromobacterium lividum and Pseudomonas sp. Four isolates (B. pantothenticus, K. Aerogenes, B megaterium and C. lividum) are choosen for further study. B pantothenticus Solubilizer greatest amounth of tricalsium phosphate indicated by increasing of orthophosphate about 12.39 mg/l in liquidmedium. Four isolates also produces phosphatase and the higest phosphatase activity is from B. pantothenticus about 1.947 ug pnitrophenol/ g/h.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words : phosphate solubilizing bacteria